A conditional mutation in a wheat (Triticum aestivum L.) gene regulating root morphology - Zeng, Deying; Ford, Brett; Doležel, Jaroslav; Karafiátová, Miroslava; Hayden, Mathew J; Rathjen, Tina M; George, Timothy S; Brown, Lawrie K; Ryan, Peter R; Pettolino, Filomena A; Mathesius, Ulrike; Delhaize, Emmanuel (TAG. Theoretical and applied genetics. Theoretische und angewandte Genetik, 2024)
Characterisation and genetic mapping of a key gene defining root morphology in bread wheat. Root morphology is central to plants for the efficient uptake up of soil water and mineral nutrients. Here we describe a conditional mutant of hexaploid wheat (Triticum aestivum L.) that when grown in soil with high Ca2+ develops a larger rhizosheath accompanied with shorter roots than the wild type. In wheat, rhizosheath size is a reliable surrogate for root hair length and this was verified in the mutant which possessed longer root hairs than the wild type when grown in high Ca2+ soil. We named the mutant Stumpy and showed it to be due to a single semi-dominant mutation. The short root phenotype at high Ca2+ was due to reduced cellular elongation which might also explain the long root hair phenotype. Analysis of root cell walls showed that the polysaccharide composition of Stumpy roots is remodelled when grown at non-permissive (high) Ca2+ concentrations. The mutation mapped to chromosome 7B and sequencing of the 7B chromosomes in both wild type and Stumpy identified a candidate gene underlying the Stumpy mutation. As part of the process to determine whether the candidate gene was causative, we identified wheat lines in a Cadenza TILLING population with large rhizosheaths but accompanied with normal root length. This finding illustrates the potential of manipulating the gene to disconnect root length from root hair length as a means of developing wheat lines with improved efficiency of nutrient and water uptake. The Stumpy mutant will be valuable for understanding the mechanisms that regulate root morphology in wheat.
Keywords: mutace; Chromosome Mapping; voda; Triticum; Water; Soil; pšenice; půda; Plant Roots; kořeny rostlin; Mutation; mapování chromozomů